Elision in English and Colloquial Iraqi Arabic: A contrastive Study (Journal of the College of Basic Education, 2022)
Elision is among these productive connected speech aspects especially when colloquial form of a language is taken into consideration. It is simply defined as the deletion of a vowel or a consonant, which should be realized by the listener if a better communication is aimed at. Different types and patterns are existent in both English and Colloquial Iraqi Arabic. Elision in both languages is realized frequently to be associated with assimilation; despite the differences in such realizations .Idiosyncratic features of each language are found to be the main source of differences between English and Arabic. Similarities are found in the general types like consonant elision, vowel elision , and historic elision , but the actual realization of each one of these three types comes to be relatively different from the other language.